Smart Electric Terminal With WEB Display Using Dreamweaver Programming In Local Network - Arif Ainur Rafiq, Supriyono, Arif Ainur Rafiq, Atika Wulandhari (International Conference on Industrial Revolution for Polytechnic Education, 2019)
Monitoring and controlling the use of electricalenergy can help in controlling the excess use of energy. Infacilitating monitoring and controlling, a smart electricalterminal application system has been designed with a WEBdisplay that is used to control electrical equipment thatintegrated into the local network. The controlled condition isthe ON/OFF from the relay that connected to the electricalterminal. This system can also monitor the state of theelectrical terminal through reading the current when there is aload attached to the electrical terminal. The Arduino webserver is used as an ON/OFF electrical terminal, and theArduino web client for current readings. Both Arduino isconnected to access point, so control and monitoring can bedone wirelessly. Monitoring of electric current uses an ACS7125A sensor, which can detect changes in current up to 5 A.Every single electrical terminal is connected to one sensor, so inthe system, it uses four ACS712 sensors. Based on the results ofthe tests, the four ACS712 sensors have been produced indifferent reading values. The difference occurs because of thedifference in response time from the four sensors, with anaverage reading between 0,04 A to 0,07 A on a no-load test.Data obtained from the results of reading electric current sentto the database, the average reading displayed in the WEB